Pengaruh Nomophobia Terhadap Konsentrasi Belajar Siswa Kelas XI di SMA Negeri 10 Kota Bogor (Program Studi Bimbingan Konseling Islam, Fakultas Tarbiyah Dan Ilmu Keguruan, Institut Ummul Quro Al-Islami Bogor, 2026)
This research aims to test whether there is an influence of nomophobia on the concentration of students at SMAN 10 Bogor in the XI grade. The sampling technique used is random sampling. The population in this study is all XI grade students totaling 324 students, and to determine the research sample, Slovin's formula is used, resulting in 179 respondents. The data used in this research is primary data in the form of a questionnaire with 212 respondents. This research method uses a quantitative approach. The data analysis technique used in this research is simple linear regression. The results of the data in this research show that there is an influence of nomophobia on students' learning concentration. This is proven by the simple linear regression test which shows a significance value of 0.000 < 0.05 with an R square value of 0.014, which means nomophobia has an influence on learning concentration. Furthermore, the results of the categorization of the level of nomophobia showed that the majority of XI grade students at SMAN 10 Kota Bogor are in the moderate category, with 174 students obtained with a percentage of 82.1%. Then, the results of the categorization of the level of students' learning concentration in XI grade at SMAN 10 Kota Bogor are also in the moderate category, as evidenced by 167 respondents with a percentage of 68.1% falling into the moderate category.